Về một bài toán tiết kiệm và tiêu dùng với thời gian rời rạc - Cường, Lê Văn; Trai, Trần Thành; Khôi, Nguyễn Kim (Journal of Computer Science and Cybernetics, 2016)
In this paper, we use the method of the dynamic programming to prove the following economic action: No matter how about property, if the salary is constant, people can’t save their earn anymore by certain time and use up their property, if not, their property will be positive.